2017
DOI: 10.3390/brainsci7070078
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Immunopathology and Treatment Update

Abstract: The treatment of multiple sclerosis (MS) has changed over the last 20 years. All immunotherapeutic drugs target relapsing remitting MS (RRMS) and it still remains a medical challenge in MS to develop a treatment for progressive forms. The most common injectable disease-modifying therapies in RRMS include β-interferons 1a or 1b and glatiramer acetate. However, one of the major challenges of injectable disease-modifying therapies has been poor treatment adherence with approximately 50% of patients discontinuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(194 citation statements)
references
References 183 publications
(355 reference statements)
3
178
0
4
Order By: Relevance
“…Various studies have illustrated the role of TGF-β1 in inciting the production of IL-10 [32,37,38], and also, it has become elucidated that TGF-β1 can trigger IL-10 through Smad4 pathway [16]. Following the same issue, TGF-β1 could repress the differentiation of naive CD4+ T cells into pathogenic Th17 ones and down-regulate the mRNA expression of IL-17 due to the immunosuppressive traits [39][40][41]. However, there are contradictory results about the impact of TGF-β1 on the differentiation of Th17 to IL-17 in a way that some of them indicated that TGF-β1 was able to trigger the differentiation of Th17 to IL-17 [42,43].…”
Section: Plos Onementioning
confidence: 99%
“…Various studies have illustrated the role of TGF-β1 in inciting the production of IL-10 [32,37,38], and also, it has become elucidated that TGF-β1 can trigger IL-10 through Smad4 pathway [16]. Following the same issue, TGF-β1 could repress the differentiation of naive CD4+ T cells into pathogenic Th17 ones and down-regulate the mRNA expression of IL-17 due to the immunosuppressive traits [39][40][41]. However, there are contradictory results about the impact of TGF-β1 on the differentiation of Th17 to IL-17 in a way that some of them indicated that TGF-β1 was able to trigger the differentiation of Th17 to IL-17 [42,43].…”
Section: Plos Onementioning
confidence: 99%
“…Interferon beta formulations were the first DMTs approved for the treatment of RMS (Dargahi et al, 2017). Peginterferon beta-1a was developed by covalently attaching a polyethylene glycol side chain to interferon beta-1a (Kieseier and Calabresi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, 50–70% of RRMS patients become chronic and develop secondary progressive MS (SPMS), which is characterized by continuous progression (Rovaris et al, ). Although previous studies identified the pathological mechanism of RRMS and developed treatments to prevent relapsing (Dargahi et al, ), the pathological mechanism of SPMS remains poorly understood. Therefore, it is necessary to elucidate the pathological molecular mechanism associated with SPMS in order to develop a therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%